The Effect of Competence, Compensation, Motivation and Commitment on the Performance of the Family Assistance Team (TPK) at the Lamongan Regency Population Control and Family Planning Office - Budi Santoso; Muhammad Imam Syairozi; Evi Fitrotun Najiah (SEAN Institute, 2024)
This study aims to analyze the influence of competency, compensation, motivation, and commitment on the performance of Family Assistance Teams (TPK) at the Lamongan Regency Population Control and Family Planning Service. The research background is based on the low TPK performance achievement of only 67.77% of the 100% target in 2022, as well as issues regarding the placement of officials whose backgrounds did not match the required competencies. This study used a quantitative method with a survey approach. The research population was all TPK members in Lamongan Regency totaling 3,108 people, with a sample of 526 respondents. Data were collected through questionnaires and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that: (1) competency has a positive and significant effect on TPK performance (coefficient = 0.444; T-stat = 14.135; p = 0.000); (2) compensation has a positive and significant effect on TPK performance (coefficient = 0.062; T-stat = 2.455; p = 0.014); (3) motivation has a positive and significant effect on TPK performance (coefficient = 0.331; T-stat = 10.015; p = 0.000); and (4) commitment has a positive and significant effect on TPK performance (coefficient = 0.272; T-stat = 8.902; p = 0.000). The R² value of 0.789 indicates that the four variables jointly explain 78.9% of the variation in TPK performance. Competency is the most dominant variable, followed by motivation, commitment, and compensation.